Valorisation of End-of-Life tyres for generating valuable resources under circular economy. (15th April 2022) - Sharma, Anita; Sawant, Ruturaj J.; Sharma, Abhishek; Joshi, Jyeshtharaj B.; Jain, Rakesh Kumar; Kasilingam, Rajkumar
Graphical abstract: Highlights: Comprehensive analytical studies of waste tyre pyrolysis products. Testing fuel value and comparing it to Bharat Stage 1–6. Using recovered Carbon Black for Styrene Butadiene Rubber Compounding. Abstract: Waste Tyre Pyrolysis is an efficient way to extract valuable products from the end-of-life tyres. The present work deals with the comprehensive analytical studies of the waste tyres by pyrolysis in a rotary kiln reactor. The main aim of the research was to understand the detailed properties of both recovered Carbon Black (rCB) and oil to make them commercially viable products and utilizing the rCB for Styrene Butadiene Rubber compounding. The pyrolytic oil was tested for its fuel value and compared with the Indian Standards (Bharat Stage 1–6). It was tested for different value-added compounds using GCMS and determining the functional groups using FTIR and NMR for commercial applications. Detailed analysis of rCB was carried out using different analytical techniques like BET, XRD and particle size distribution so as to understand the physical nature of synthesized rCB. Addition of tyre rCB was found to have increase in tensile strength and associated properties of vulcanization of rubber product without any negative impact. Significant improvement was observed on tear strength properties while adding the rCB compared to that of without rCB addition or addition of carbon black. This proved that there exists the reinforcing characteristics of the rCB like standard carbon black.